First record of the long-winged harrier, Circus buffoni (Aves, Accipitridae) from the Northeastern extreme of Brazil - Pequeno, José Arthur Felipe; Melo, Hilda Raianne Silva de; Pichorim, Mauro (Brazilian Journal of Science, 2025)
We present the first record of the Long-winged harrier, Circus buffoni (Gmelin, 1788), from the state of Rio Grande do Norte, in the Northeastern extreme of Brazil, specifically, the East Potiguar Microregion, which is located within the Atlantic Forest phytogeographic domain. During the study, we recorded at least two individuals between January and June, and recorded their foraging behavior and predation events. We also compiled all published data available on C. buffoni, as well as records from ornithological collections and online databases, which resulted in a total of 13 documented records for the Brazilian Northeast. Breeding populations of C. buffoni are known to exist in both northern and southern South America, providing conflicting evidence on the possible origin of the study individuals and their migratory patterns in Brazil. Given the persistent lacunas in our understanding of the dispersal patterns of Circus buffoni, we recommend further surveys in areas with similar habitats to provide more comprehensive data for defining the species' distribution in South America and its migratory patterns.